G500(P) An examination of the safety and efficacy of high flow nasal cannula therapy for acute severe asthma and viral induced wheeze in paediatric critical care. (27th April 2016) - Alcock, A; Thompson, C; Robertson, R; Ali, T
Abstract : Aims: The purpose of this abstract is to examine the efficacy and safety of high flow nasal cannula (HFNC) therapy in children over 1 year old admitted to paediatric critical care with a diagnosis of acute severe asthma or viral induced wheeze (VIW). Methods: A retrospective study of all children over 1 year old admitted to our paediatric critical care unit with a diagnosis of acute asthma or VIW who received HFNC therapy between March 2011 and June 2015 was made. Children who were already intubated and children who did not receive HFNC therapy were excluded. All children with a diagnosis of bronchiolitis or pneumonia were excluded. The medical records and the critical care database were examined retrospectively for patient demographics, details of illness and complications. Results: 58 children were identified as fitting our inclusion criteria. The data showed that HFNC use was not limited to any particular age group but was used more in those less than 5 years old: Figure 1 . The HFNC therapy was given for between 1 and 220 h with a median duration of 28 h: Figure 2 . In regards to complications none of the 58 children who received HFNC therapy suffered hypoxia, or developed a pneumothorax. Four required subsequent intubation. There were no fatalities: Fig.3. Conclusions: HFNC therapy is increasingly used for acute respiratory failure in children. Although it has been studied in a variety of paediatric respiratory conditions, up until now there has been no study of its safety or efficacy specifically in children with acute asthma or VIW. In combination with standard treatment for acute severe asthma, HFNC therapy appears to be safe and efficacious. 4 of 58 patients (<7%) required subsequent intubation and ventilation. No patients suffered complications. We suggest that HFNC therapy may be safely combined with standard therapy in acute severe asthma or viral induced wheeze in the critical care and emergency setting. A randomised control trial will be necessary to determine if HFNC therapy reduces intubation rates.